Visual configuration of two species of Falconidae with different foraging ecologies. (11th September 2017) - Potier, Simon; Bonadonna, Francesco; Martin, Graham R.; Isard, Pierre‐François; Dulaurent, Thomas; Mentek, Marielle; Duriez, Olivier
Abstract : Significant interspecific differences in avian vision occur, even in congeneric species, and these have been correlated with differences in the perceptual challenges associated with foraging. Although diurnal raptors are assumed to be mainly visually guided in their foraging, they differ markedly in their foraging tactics and this may result in different visual demands. Among the Falconidae (Falconiformes), most falcons forage mainly on the wing for highly mobile prey, whereas caracaras forage on the ground for carrion and insects. We assessed whether Saker Falcon Falco cherrug and Southern Caracara Caracara plancus differ in their visual abilities by determining the visual fields and foveal characteristics of both species. Using an ophthalmoscopic reflex technique, we found a higher degree of binocular overlap in the caracaras than in the falcons. The high binocular overlap (47°) of the Southern Caracara may facilitate object manipulation (e.g. moving rocks) when foraging. We used an ultra‐high resolution spectral‐domain optical coherence tomography to determine foveal characteristics. We found two foveas (depressions in the retina where high visual resolution is expected) in the falcons (one central and one temporal) but only a central fovea in the caracaras. The presence of a shallower temporal fovea in Saker Falcons may help to fixate visually upon a highly mobile prey item during pursuit. We conclude that these differences in visual field configurations and foveal characteristics reflect different foraging demands, suggesting that the extraction of visual information is finely tuned to the demands of their foraging tactics.